2022
DOI: 10.3390/biom12121855
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Bulk RNA-Seq and Single-Cell RNA-Seq Unveils Novel Prognostic Biomarkers in Multiple Myeloma

Abstract: Molecular heterogeneity has great significance in the disease biology of multiple myeloma (MM). Thus, the analysis combined single-cell RNA-seq (scRNA-seq) and bulk RNA-seq data were performed to investigate the clonal evolution characteristics and to find novel prognostic targets in MM. The scRNA-seq data were analyzed by the Seurat pipeline and Monocle 2 to identify MM cell branches with different differentiation states. Marker genes in each branch were uploaded to the STRING database to construct the Protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Ubiquinone oxidoreductase subunit A6(NDUFA6) is an accessory subunit of NADH. Several researches have reported that NDUFA6 was correlated with prognosis of multiple myeloma and was involved in mitochondrial fitness to promote proliferation in glioblastoma cells [ 44 , 45 ]. The p-value of TIMM50 was to be the most significant by multifactorial COX regression analysis and was a potential marker of EC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquinone oxidoreductase subunit A6(NDUFA6) is an accessory subunit of NADH. Several researches have reported that NDUFA6 was correlated with prognosis of multiple myeloma and was involved in mitochondrial fitness to promote proliferation in glioblastoma cells [ 44 , 45 ]. The p-value of TIMM50 was to be the most significant by multifactorial COX regression analysis and was a potential marker of EC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 By integrating scRNA-seq data to identify specific cell types or subpopulations with bulk RNA sequencing data to identify differentially expressed genes or pathways, more accurate and reliable biomarkers can be identified. [29][30][31][32] These biomarkers can be used for diagnosis, prognosis, and personalized treatment of diseases. Therefore, integrating scRNA-seq and bulk RNA sequencing can provide a more comprehensive understanding of the molecular mechanisms underlying disease and improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%